2006
DOI: 10.1016/s0022-5347(05)00356-3
|View full text |Cite
|
Sign up to set email alerts
|

Toe Spreading Ability in Men With Chronic Pelvic Pain Syndrome

Abstract: Background: We examined toe-spreading ability in subjects with chronic pelvic pain syndrome (CPPS) to test the hypothesis that subjects with CPPS could have deficiencies in lower extremity functions innervated by sacral spinal roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…For example, it has been demonstrated that there is incomplete toe spreading much more commonly in men with CPPS than those without. 36 One case series has documented that a program integrating trigger-point release in the myofascia of the perineum with relaxation training c a n p r o d u c e s i g n i f i c a n t p a i n relief. 37 This theory is corroborated by the historical use of kava (Piper methysticum) root as a bladder and urinary-tract sedative.…”
Section: Neurologic Issuesmentioning
confidence: 99%
“…For example, it has been demonstrated that there is incomplete toe spreading much more commonly in men with CPPS than those without. 36 One case series has documented that a program integrating trigger-point release in the myofascia of the perineum with relaxation training c a n p r o d u c e s i g n i f i c a n t p a i n relief. 37 This theory is corroborated by the historical use of kava (Piper methysticum) root as a bladder and urinary-tract sedative.…”
Section: Neurologic Issuesmentioning
confidence: 99%